Specific entry of Helicobacter pylori into cultured gastric epithelial cells via a zipper-like mechanism. - Kwok, T.; Backert, Steffen; Schwarz, H.; Berger, J.; Meyer, Thomas F. (Infection and Immunity, 2002)
Although Helicobacter pylori has generally been considered an extracellular pathogen, a number of in vitro infection experiments and biopsy examinations have shown that it is capable of occasionally entering mammalian host cells. Here, we characterized this entry process by using AGS cells as a host cell model. In gentamicin protection-invasion assays, the number of H. pylori colonies recovered was lower than that for Salmonella enterica serovar Typhimurium X22, Escherichia coli expressing InvA, and Yersinia enterocolitica YO:9 grown at 25 degrees C but higher than that for Neisseria gonorrhoeae VP1 and Y. enterocolitica YO:9 grown at 37 degrees C. At the ultrastructural level, the entry process was observed to occur via a zipper-like mechanism. Internalized H. pylori was bound in tight LAMP-1-containing vacuoles in close association with condensed filamentous actin and tyrosine phosphorylation signals. Wortmannin, a potent inhibitor of phosphatidylinositol 3-kinase, and calphostin C, an inhibitor of protein kinase C, both inhibited the entry of H. pylori in a sensitive and dose-dependent manner; however, the level of entry was enhanced by sodium vanadate, an inhibitor of tyrosine phosphatases and ATPases. Furthermore, the cytokine tumor necrosis factor alpha antagonized the entry of H. pylori into AGS cells. Collectively, these results demonstrate that the entry of H. pylori into AGS cells occurs via a zipper-like mechanism which involves various host signal transduction events.